Identification of blaSHV and blaTEM extended spectrum beta-lactamase genes in Klebsiella pneumoniae in the dairy wastewater, East Java Province, Indonesia - FIDI NUR AINI EKA PUJI DAMEANTI; SHEILA MARTY YANESTRIA; MUSTOFA HELMI EFFENDI; HANI PLUMERIASTUTI; WIWIEK TYASNINGSIH; EMMANUEL NNABUIKE UGBO; RAHAYU SUTRISNO; M. ALI AKRAM SYAH SAFRI (Society for Indonesian Biodiversity, 2023)
Abstract. Dameanti FNAEP, Yanestria SM, Effendi MH, Plumeriastuti H, Tyasningsih W, Ugbo EN, Sutrisno R, Safri MAAS. 2023. Identification of blaSHV and blaTEM extended spectrum beta-lactamase genes in Klebsiella pneumoniae in the dairy wastewater, East Java Province, Indonesia. Biodiversitas 24: 6092-6099. Klebsiella pneumoniae infection in dairy cows causes various livestock production hazards and threatens public health because it acts as a Multi-Drug Resistance Bacteria (MDRB), especially Extended-Spectrum Beta-Lactamase (ESBL) strains. Livestock wastewater is a repository for commensal isolates including K. pneumoniae and potentially can be a reservoir for ESBL spreaders for the environment. The aim of this study was to identify the blaSHV and blaTEM ESBL genes in K. pneumoniae from wastewater of dairy cattle farms in East Java Province. This study used a sample of 342 dairy farm wastewater isolated on 2% BPW media from 6 cities/regencies with the highest population of dairy cows in East Java, Indonesia, namely Pasuruan District, Malang District, Tulungagung District, Blitar District, Batu City and Kediri District. Samples were identified on MCA media, Gram staining, EMBA, and biochemical tests. Confirmation of ESBL phenotypically used the Double Disc Synergy Test (DDST) method and the Polymerase Chain Reaction (PCR) test to detect the ESBL gene. The result showed that bacterial isolation and identification were 14.32% (49/342), confirmed K. pneumoniae. DDST confirmation results of ESBL-producing K. pneumoniae isolates from the wastewater of dairy farms in East Java obtained were 5.55% (19/342). The sample was continued with the PCR test showing positive for the blaSHV gene 63.1% (12/19) and blaTEM 31.57% (6/19). In conclusion, the ESBL gene blaSHV and blaTEM identification in K. pneumoniae isolates, indicate that wastewater from dairy farms has the potential to be a reservoir of ESBL carriers in the environment and pose a threat to public health in East Java Province, Indonesia.